The first mitochondrial genome data of an old world fruit bat, Cynopterus sphinx from Malaysia - Jaharia, Puteri Nur Syahzanani; Mohd Azman, Shahfiz; Munian, Kaviarasu; Zakaria, Nur Alwani; R. Richterd, Stine; Omar, Mohd Shahir Shamsir; Mohd Salleha, Faezah (Springer, 2021)
We assembled the complete mitogenome of Cynopterus sphinx (Vahl, 1797) of the family Pteropodidae originating from Malaysia. The total mitogenome size was 16,710bp which consists of 37 genes (13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one control region). A phylogenetic and BLASTn result showed the mitogenome sequence in this study varies by nearly 7% (93.48% similarity) from the same species in Cambodia. The next closest match of BLASTn was at 92% similarity to the C. brachyotis. This suggests the species-complex in Cynopterus sp. has given rise to the genetic variability.